Pathogenicity potential of enterococci isolated from a Veterinary Biological Isolation and Containment Unit - Geraldes, Catarina; Araújo, Catarina; Pinheiro, Ana Catarina; Afonso, Mónica; Carapeto, Sandra; Verdial, Cláudia; Cunha, Eva; Abreu, Raquel; Tavares, Luís; Chambel, Lélia; Gil, Solange; Oliveira, Manuela (Frontiers in Veterinary Science, 2024)
IntroductionEnterococcus are considered an important genus in terms of Hospital-Acquired Infections (HAIs), which means that their characterization regarding resistance and virulence profiles in the hospital environment is of extreme importance. This article addresses this issue through the characterization of enterococci collected from a Veterinary Biological Isolation and Containment Unit (BICU).MethodsA total of 73 isolates, collected from different surfaces of a Veterinary BICU, were identified as Enterococcus through PCR at species level, after which 34 isolates were selected as representatives using (GTG)5 fingerprinting. These isolates were further characterized phenotypically in terms of antimicrobial resistance through disk diffusion and of virulence factors’ expression.ResultsThe majority of the enterococci isolated presented resistance to erythromycin (79.4%), ampicillin (73.5%), amoxicillin-clavulanic acid (70.6%), tetracycline (67.6%), ciprofloxacin (58.8%) and levofloxacin (50.0%), and were able to produce hemolysin (88.2%) and biofilm (82.3%). Furthermore, in terms of pathogenicity, three isolates (8.8%) were classified as high threats and two (5.9%) as moderate threats.DiscussionThe degree of resistance, production of virulence factors and the percentage of isolates classified as moderate or high threat means that a constant vigilance of such strains in veterinary units, but also in clinics and hospitals in general, is an important tool in terms of infection prevention and consequent reduction of HAIs.